2021
DOI: 10.1055/a-1521-6318
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of poor healing and poor squamous regeneration after radiofrequency ablation therapy for early Barrett’s neoplasia

Abstract: Background Although endoscopic eradication therapy with radiofrequency ablation (RFA) is effective in most Barrett’s Esophagus (BE) patients, some might experience poor healing (PH) and/or poor squamous regeneration (PSR). We aimed to evaluate PH/PSR incidence and treatment outcomes. Methods We included all patients treated with RFA for early BE neoplasia, from a nationwide Dutch registry based on a joint treatment protocol. PH was defined as active inflammatory changes or visible ulcerations ≥3 months post-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Nevertheless, in clinical practice, we regularly see patients in whom resection followed by ablation fails to achieve complete squamous epithelialization of the esophagus. 3 Thus, we observe inadequate healing with fibrin-covered ulceration, or healing with undesired Barrett's mucosa (neo-Barrett's). Some studies have reported BE recurrence after previous complete endoscopic therapy.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, in clinical practice, we regularly see patients in whom resection followed by ablation fails to achieve complete squamous epithelialization of the esophagus. 3 Thus, we observe inadequate healing with fibrin-covered ulceration, or healing with undesired Barrett's mucosa (neo-Barrett's). Some studies have reported BE recurrence after previous complete endoscopic therapy.…”
Section: Introductionmentioning
confidence: 81%
“…We observed wound healing disorders in almost every 8th patient in our cohort, which is in concordance with previous and recently published studies. 3 , 20 That means that a non-healing BE after endoscopic therapy is a frequent problem and must be considered by interventional endoscopists. The definition of complete eradication of intestinal metaplasia varies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although ablation spares the patient the morbidity of many endoscopic resection procedures, "escape resection" should be used when ablation fails after repeated procedures. Indeed, the increased risk of neoplastic progression of the patients with poor squamous regeneration after ablation should be kept in mind [37].…”
Section: Common Mistakes On Ablationmentioning
confidence: 99%
“…Following their previous RFA outcome study, van Munster et al [4] present results of an observational study, again based on data from the Dutch Barrett's Expert Center registry, in this issue of Endoscopy. The study provides a detailed analysis of the characteristics and outcomes of patients with neoplastic BE who had a poor response to RFA therapy.…”
mentioning
confidence: 98%